2022
DOI: 10.3390/ijms232113631
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular Profiling by MALDI-TOF Mass Spectrometry in Food and Beverage Analyses

Abstract: Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) has frequently been applied to the analysis of biomolecules. Its strength resides not only in compound identification but particularly in acquiring molecular profiles providing a high discriminating power. The main advantages include its speed, simplicity, versatility, minimum sample preparation needs, and a relatively high tolerance to salts. Other benefits are represented by the possibility of automation, high through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…The differences in molecular weight indicated the successful conjugation of A6 peptide to HSA through SMCC. The matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MADLI-TOF-MS) was further applied to analyze the obtained peptide-conjugated albumin [ 41 ]. The results revealed that the molecular-related ion peaks of HSA and different degrees of A6-HSA were at m/z 66,464, 67,993 and 70,119, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The differences in molecular weight indicated the successful conjugation of A6 peptide to HSA through SMCC. The matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MADLI-TOF-MS) was further applied to analyze the obtained peptide-conjugated albumin [ 41 ]. The results revealed that the molecular-related ion peaks of HSA and different degrees of A6-HSA were at m/z 66,464, 67,993 and 70,119, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to future requirements, a bioinformatics‐based approach should be applied to investigate protein assignment and provide robust identification and differentiation procedures of foodborne pathogens at the strain level. In recent years, it has occurred that a PCA‐based approach was used to increase the share of peaks separating and reducing the weighting of the common peak in the datasets from closely related organisms (Šebela, 2022). The identification of a potential biomarker peak by PCA was an important clue for further studies (Sassi, Arena, & Scaloni, 2015; Yu, Yu, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Little progress regarding the most suitable matrix has been made since the first TAG analysis by MALDI. DHB and super-DHB (a 9:1 mixture of DHB and 2-hydroxy-5-methoxybenzoic acid) were used in the majority of cases [ 41 ]. The poor interest in matrix optimization is presumably due to the fact that the majority of TAG is available in major amounts, and there is no need to increase the sensitivity of detection.…”
Section: Which Matrix Is Most Suitable For Individual Lipid Classes?mentioning
confidence: 99%